2021
DOI: 10.3390/ijerph18042201
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cause of Household Carbon Lock-In for Chinese Urban Households

Abstract: Household energy conservation is an important contributor to achieve the carbon emission reduction target. However, the actual energy-saving effect of Chinese households is under expectation. One reason for this is because household energy consumption is locked in at a certain level, which has become an obstacle to household carbon emission reduction. In order to reduce this obstacle, this study explored the cause of household carbon lock-in based on grounded theory, targeting newly furnished households. A the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Some scholars have argued that the carbon lock-in effect is one of the major obstacles in the transition to a low-carbon economy and that carbon lock-in can lead to greater welfare losses in the absence of regulatory conditions [18]. This was also found when analyzing the energy consumption behavior of urban households [19]. This is because the path of industrial countries when building industrial systems is locked in the fossil energy-based energy system.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some scholars have argued that the carbon lock-in effect is one of the major obstacles in the transition to a low-carbon economy and that carbon lock-in can lead to greater welfare losses in the absence of regulatory conditions [18]. This was also found when analyzing the energy consumption behavior of urban households [19]. This is because the path of industrial countries when building industrial systems is locked in the fossil energy-based energy system.…”
Section: Introductionmentioning
confidence: 92%
“…It also brought about quite serious pollution events such as the London toxic fog that caused thousands of deaths [15,16]. Some studies have shown that the economy's structure based on fossil energy sources has also created certain carbon lock-in and energy rebound effects [17][18][19][20]. Some scholars have argued that the carbon lock-in effect is one of the major obstacles in the transition to a low-carbon economy and that carbon lock-in can lead to greater welfare losses in the absence of regulatory conditions [18].…”
Section: Introductionmentioning
confidence: 99%